Toward a better understanding of transition from paediatric to adult care in type 1 diabetes: A qualitative study of adolescents. Issue 5 (7th January 2022) - Ladd, Jennifer M.; Reeves‐Latour, Jonathan; Dasgupta, Kaberi; Bell, Lorraine E; Anjachak, Nadia; Nakhla, Meranda
Abstract: Aims: Type 1 diabetes is associated with significant morbidity, with an increasing risk of acute diabetes‐related complications in adolescence and emerging adulthood. Purposeful transition from paediatric to adult‐oriented care could mitigate this risk but is often lacking. Detailed understanding of the perspectives of adolescents in their final year of paediatric care is essential to inform delivery of transition care programs. Methods: We conducted semi‐structured interviews with adolescents (aged 17 years) with type 1 diabetes at an academic institution from April 2017 to May 2018. Participants were recruited through convenience sampling. Sixty‐one interviews were transcribed for analysis. Coding followed the principles of thematic analysis. Results: Thirty‐six percent of participants were male, and participants were from diverse socioeconomic backgrounds. We found three overarching themes in our analysis: first, difficulties navigating changing relationships with parents and healthcare teams; second, the need to increase type 1 diabetes self‐management and differing comfort levels based on age of diagnosis; and third, perceived responsibilities for transition care preparation (for both the paediatric team and adolescents themselves) focused not only on type 1 diabetes‐specific skills but also on healthcare system structures. Conclusions: Our findings suggest that novel transition programs addressing changing inter‐personal relationships, disease‐specific self‐management (adapted for age of diagnosis), and healthcare system navigation, supported by parents and peers, may be needed to improve transition care for adolescents with type 1 diabetes.